Exploring the Perceived Usefulness and Effect of AI Writing Tools in Enhancing the Quality of Written Outputs of Senior High School Students - Discutido, Roy A. (Future Science / FSH-PH Publications, 2025)
While AI writing tools promise efficiency and productivity, educators are concerned about their potential threat to academic integrity. This study focuses on identifying the AI writing tools used by students, assessing each tool’s perceived usefulness based on its functionality, and exploring students' views on the impact of AI writing tools in enhancing their written output. A quantitative method, using a survey questionnaire, was employed to determine the AI writing tools students use and their perceived usefulness. A qualitative method, via focus group discussions, was also utilized to explore students' views on using AI writing tools to enhance their academic work. The results show that students are exposed to various AI writing tools, with Google Translate being popular for language translation, Quillbot for summarizing and paraphrasing, and ChatGPT for content generation and other writing-related tasks. Students perceived AI writing tools as very useful for enhancing their academic papers, as they increase their confidence in writing and improve productivity and efficiency. However, due to potential inaccuracies in generated content, students expressed skepticism on fully relying on AI writing tools. They indicated that they have become more vigilant when using these tools to avoid plagiarism and prevent incorporating false information and sources. The study suggests that educational institutions could develop guidelines or implement policies on the ethical use of AI writing tools to promote academic integrity. Schools may also encourage responsible use of these tools to cultivate a culture of honesty.